Non‐LTE iron abundances in cool stars: The role of hydrogen collisions. Issue 8 (30th September 2016) - Ezzeddine, R.; Merle, Th.; Plez, B.
Abstract: In the aim of determining accurate iron abundances in stars, this work is meant to empirically calibrate H‐collision crosssections with iron where no quantum mechanical calculations have been published yet. Thus, a new iron model atom has been developed which includes hydrogen collisions for excitation, ionization, and charge transfer processes. We show that collisions with hydrogen leading to charge transfer are important for an accurate non‐LTE modeling. We apply our calculations on several benchmark stars including the Sun, the metal‐rich star α Cen A, and the metal‐poor star HD 140283.